A systematic review of factors that influence the acceptability of vaccines among Canadians. Issue 2 (8th January 2021) - Gates, Allison; Gates, Michelle; Rahman, Sholeh; Guitard, Samantha; MacGregor, Tara; Pillay, Jennifer; Ismail, Shainoor J.; Tunis, Matthew C.; Young, Kelsey; Hardy, Kendra; Featherstone, Robin; Hartling, Lisa
Highlights: >100 studies on vaccine acceptability among Canadians were published over 5 years. The perceived safety and importance of the vaccine were common influential factors. Vaccination history and a healthcare provider's recommendation influenced uptake. Reminder systems and policies that improve access may increase uptake and coverage. Abstract: Background: Canada's National Advisory Committee on Immunization (NACI) provides guidance on the use of vaccines in Canada. To support the expansion of its mandate to include considerations for vaccine acceptability when making recommendations, the NACI Secretariat developed a matrix of factors that influence acceptability. To inform and validate the matrix, we systematically reviewed evidence for factors that influence vaccine acceptability, and for interventions aimed at improving acceptability. Methods: On 10–11 October 2018 we searched four bibliographic databases, the Theses Canada Portal, and ClinicalTrials.gov. Two reviewers agreed on the included studies. From each study, we extracted information about the participants, intervention or exposure, comparator, and relevant outcomes. Due to heterogeneity in the reported factors and acceptability indicators we synthesized the findings narratively. We appraised the certainty of evidence using GRADE. For each vaccine-preventable disease we populated a matrix of factors for which there was evidence of an influence on acceptability. Results: One hundred studies (>1 million participants) contributed data relevant to the public, 16 (6191 participants) to healthcare providers, and three (84 participants) to policymakers. There were 43 intervention studies ( 2 million participants). Across vaccines, we identified low certainty evidence for 70 factors relevant to the general population, 56 to high-risk groups, and 30 to healthcare providers. The perceived safety and importance of the vaccine, vaccination history, and receiving a recommendation from a healthcare provider were common influential factors. We found low certainty evidence that reminders for childhood vaccines and policies or delivery models for rotavirus vaccines could improve uptake and coverage. Evidence for other interventions was of very low certainty. Conclusions: The NACI vaccine acceptability matrix is useful for categorizing acceptability factors for the general public. Reminder systems may improve the uptake of childhood vaccines. Policies that make the rotavirus vaccine universally available and easily accessible may improve coverage. Funding: This systematic review was completed under contract to the Public Health Agency of Canada, Contract #4600001536.